Learning object for teacher training oriented to develop skills to use oer - Ahabael LUGO LÓPEZ; Fernando Gustavo LOZANO MARTÍNEZ; María Soledad RAMÍREZ MONTOYA (Ediciones Universidad de Salamanca, 2014)
This article aims to present the results of an investigation related to the design and use of an Open Learning Object. Using a qualitative methodology approach and electronic applied interviews to some of the experts who were in charge of evaluate the Learning Object, the following research question was answered: How much does the Open Educational Resource designed to enhance educational practice, meets a set of established quality criteria that characterizes the Open Learning Objects? The obtained results indicate that the learning object fulfilled effectively with the standards and specifications concerning the pedagogical and technological aspects, however there were some other aspects such as misconceptions, activities and evaluation that were considered to be reviewed and even changed in order to considered the Open Learning Object as a high quality one. It is worthy of note the fact that the subject of the present investigation is considered an innovation and also a necessary and useful tool for the current demands of teaching work.